Removal of Swarms and Colonies for Pest Control Operators - Michael K. O'Malley; Jamie D. Ellis; Philip G. Koehler (EDIS, 2009)
ENY-145, a 12-page illustrated fact sheet by Michael K. O’Malley, Jamie D. Ellis, and P. G. Koehler, outlines for pest control operators the standard operating procedures for removing swarms and colonies. Includes additional resources and contacts. Published by the UF Department of Entomology and Nematology, November 2008.